The existence and persistence of the pay-per-use bias in car sharing services - Dowling, Katharina,Manchanda, Puneet,Spann, Martin (Collaborative Research Center Transregio 190, 2019)
A key benefit of using car sharing services (relative to car ownership) is that they are more cost effective. Car sharing firms offer a menu of pricing plans to make this happen. The two most common plans are flat-rate and pay-per-use pricing. However, little is known about how consumers choose among these pricing plans. In this study, we analyze consumers’ choices between pay-per-use and flat-rate pricing using data from a car sharing provider in a large European city. We show that over 40% of customers make nonoptimal pricing plan choices (i.e., they do not choose the cost minimizing plan). In contrast to previous research, we find a prevalent and time-persistent pay-per-use bias; i.e., we find little evidence that consumers “learn”. We propose three potential explanations for the existence and persistence of this bias. First, we suggest that customers underestimate their usage. Second, we propose that customers have a preference for flexibility, leading them to pay more. Finally, we show that the physical context, such as weather, increases the likelihood of a pay-per-use bias. We suggest that the pay-per-use bias may be the prevalent tariff choice bias in the Sharing Economy.
10419/208093
Keywords: Graue Literatur; Sharing Economy; Car Sharing; Pricing; Pay-per-use Bias; Flat-rate Bias